Protective mechanism of dried blood spheroids: stabilization of labile analytes in whole blood, plasma, and serum. Issue 22 (12th October 2021) - Frey, Benjamin S.; Damon, Deidre E.; Allen, Danyelle M.; Baker, Jill; Asamoah, Samuel; Badu-Tawiah, Abraham K.
Abstract : Dried blood spheroid prepared on hydrophobic paper substrate enables the stabilization of red blood cells at room temperature. Abstract : Three-dimensional (3D) dried blood spheroids form when whole blood is deposited onto hydrophobic paper and allowed to dry in ambient air. The adsorbed 3D dried blood spheroid present at the surface of the hydrophobic paper is observed to offer enhanced stability for labile analytes that would otherwise degrade if stored in the traditional two-dimensional (2D) dried blood spot method. The protective mechanism for the dried blood spheroid microsampling platform was studied using scanning electron microscopy (SEM), which revealed the presence of a passivation thin film at the surface of the spheroid that serves to stabilize the interior of the spheroid against environmental stressors. Through time-course experiments based on sequential SEM analyses, we discovered that the surface protective thin film forms through the self-assembly of red blood cells following the evaporation of water from the blood sample. The bridging mechanism of red blood cell aggregation is evident in our experiments, which leads to the distinct rouleau conformation of stacked red blood cells in less than 60 min after creating the blood spheroid. The stack of self-assembled red blood cells at the exterior of the spheroid subsequently lyse to afford the surface protective layer detected to be approximately 30 μm in thickness after three weeks of storage in ambient air. We applied this mechanistic insight to plasma and serum to enhance stability when stored under ambient conditions. In addition to physical characterization of these thin biofilms, we also used paper spray (PS) mass spectrometry (MS) to examine chemical changes that occur in the stored biofluid. For example, we present stability data for cocaine spiked in whole blood, plasma, and serum when stored under ambient conditions on hydrophilic and hydrophobic paper substrates.